MANAJAMEN RISIKO K3 PADA PETUGAS PEMADAM KEBAKARAN PROVINSI DKI JAKARTA DENGAN METODE HIRADC TAHUN 2022 - Suci Puspita Sari (2022)
Fire is a great and harmful hazard. The increasing incidence of fires makes the intensity of firefighters have a high risk. A method is needed to conduct a risk assessment on firefighters. In DKI Jakarta, there will be an increase in cases in 2021 and cause 76 fatalities. HIRADC (Hazard Identification Risk Assessment and Determining Control) is a method in K3 management to identify and evaluate hazards in the work environment and can provide methods to control or eliminate identified hazards. This research uses a qualitative research type. Based on the research results, it is known that there are 24 work activities, 7 low-level risks (Risk Matrix Values 1-4), 25 moderate risks (Risk Matrix Values 5-12) and 5 high-level risks (Risk Matrix Values 15-25). It was concluded that the risks contained in firefighting work activities were dominated by medium and high level risks. Control recommendations are given in accordance with the control hierarchy, namely elimination, substitution, engineering, administrative and PPE